2002
DOI: 10.1002/1522-2675(200210)85:10<3144::aid-hlca3144>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of -Peptide Models: Intrinsic Preferences of Helical Structures

Abstract: Dedicated to Professor Dieter Seebach on the occasion of his 65th birthday b-Peptides form various secondary structures, such as 14-helix, 12-helix, 10/12-helix, 10-helix, 2 8 -ribbon, C6-ribbon, and pleated-sheet. Thus, it is useful to understand the intrinsic backbone conformational preferences of these basic structures. By using a simple repeating-unit method, we have calculated the preferences of C6-ribbon, b-strand, 10/12-helix, 14-helix, 12-helix, 10-helix, and 2 8 -ribbon of a series of poly-b-alanine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 13 publications
2
31
0
Order By: Relevance
“…The reference structures were built based on ideal backbone dihedral angles values for a 3 14 ‐helix. 33 A conformational clustering analysis, performed as described in previous studies, 18, 44 was carried out on the separate and combined trajectories of the (depsi)peptides using structures at 10 and 20 ps intervals, respectively, and a rmsd similarity criterion of 0.1 nm. 18 The hydrogen‐bond analysis uses as criterion for defining a hydrogen bond a maximum hydrogen‐acceptor distance of 0.25 nm and a minimum donor atom‐hydrogen‐acceptor angle of 135°.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference structures were built based on ideal backbone dihedral angles values for a 3 14 ‐helix. 33 A conformational clustering analysis, performed as described in previous studies, 18, 44 was carried out on the separate and combined trajectories of the (depsi)peptides using structures at 10 and 20 ps intervals, respectively, and a rmsd similarity criterion of 0.1 nm. 18 The hydrogen‐bond analysis uses as criterion for defining a hydrogen bond a maximum hydrogen‐acceptor distance of 0.25 nm and a minimum donor atom‐hydrogen‐acceptor angle of 135°.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of the side chains on the conformational propensity of a peptide is more intricate, and results from a balance between a modulation of the local conformational preferences of the backbone (at residue level) and a global influence associated with medium‐ to long‐range electrostatic, Van der Waals, and inter‐residue steric interactions. 27, 33, 34 As an example of the second type of influence, hydrophobic or ionic (salt‐bridge) interactions between side chains at positions i and i + 3 along the sequence tend to stabilize the 3 14 ‐helical conformation. 25, 35, 36…”
Section: Introductionmentioning
confidence: 99%
“…The 10/12‐mixed helix, unique to β peptides, was discovered by Seebach et al4 in β 2 /β 3 ‐dipeptide repeats. Theoretical studies by Hofmann and co‐workers7a and Wu et al7b,c predicted that 10/12 and 12/10 helices are energetically the most favored secondary structures in β peptides in solution. Subsequently, Kessler and co‐workers8 used a cyclic sugar β‐amino acid and β‐hGly repeats to obtain such mixed helices.…”
Section: Methodsmentioning
confidence: 99%
“…The important features of the β‐ and γ‐peptide helices are that they can fold into helices with a chain length of as short as six and four residues when compared with about 10–12 residues for natural α‐peptides in organic solvents, respectively, and that the helix type, the helicity [right‐handed ( P ) and left‐handed ( M )], and the direction of the helix macrodipole (i.e., the orientation of H‐bonds) can readily be controlled by the substitution pattern or/and stereochemistry of residues. Besides experimental measurements, considerable molecular dynamics simulations and ab initio calculations have also been performed to obtain the conformational preferences and the effects of substituents on folding propensities of β‐peptides and all possible periodic structures having the characteristic sizes and patterns of the H‐bonded pseudocycles for hexapeptides of γ‐aminobutyric acid (γAbu) and its vinylogous derivatives . In particular, it is found that the 14‐ and 9‐helices of the γAbu hexapeptide are most preferred in the gas phase; however, its 12‐ and 14‐helices become most probable in water …”
Section: Introductionmentioning
confidence: 99%